2011
DOI: 10.1002/chp.20146
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Collaborative Program on Smoking Cessation: Translating Outcomes Framework Into Practice

Abstract: The program had an overall positive impact on the measured variables for clinicians and their patients. Use of 1 outcomes assessment framework acceptable to all members of the collaborative, common measures and evaluation techniques, and centralized data repositories contributed to the success of the program evaluation reported here and is recommended to others who are considering a collaborative program evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Several case studies have demonstrated that education, specifically Performance Improvement (PI) CME, improves clinical practice. [28][29][30][31][32][33][34][35] However, to our knowledge, data do not exist regarding the use of the PI CME format in the specialty of dermatology. PI CME helps physicians evaluate their practice and implement evidencebased strategies to overcome identified gaps, then remeasure their performance after these strategies have been implemented in their practice.…”
mentioning
confidence: 65%
“…Several case studies have demonstrated that education, specifically Performance Improvement (PI) CME, improves clinical practice. [28][29][30][31][32][33][34][35] However, to our knowledge, data do not exist regarding the use of the PI CME format in the specialty of dermatology. PI CME helps physicians evaluate their practice and implement evidencebased strategies to overcome identified gaps, then remeasure their performance after these strategies have been implemented in their practice.…”
mentioning
confidence: 65%
“…In particular, evidence-based adult and organizational learning principles were drawn from articles that included but were not limited to Marinopolous and colleagues, 6 Moore and colleagues, 7 and Staker. 8 Furthermore, the evaluation results reported in the article in this supplement by Shershneva and colleagues 9 demonstrated that improvements in performance and patient outcomes were achieved.…”
Section: Alliance Competency Area 1: Adult and Organizational Learninmentioning
confidence: 89%
“…Combined, these needs data helped prioritize and plan intervention content to focus on areas of relatively greater needs more than those of relatively smaller needs. The competency framework was carried through to the outcomes measures as well: as shown in this supplement by Shershneva et al 11 (FIGURE 1), greater improvements were made in the areas of Advise, Assist, and Arrange compared to the Ask and Assess competencies. These changes correspond to what would be expected based on the size of gaps in needs assessment data (FIGURE 2).…”
Section: Discussionmentioning
confidence: 99%
“…Our approach was to develop a series of clinical competency statements that could serve as the basis for developing tools and instruments to: assess learning needs, develop educational activities, and assess the outcomes of those activities. These competencies also served as the basis of tools for a summative assessment of the entire CS2day initiative, as reported elsewhere in this supplement (see the article by Shershneva et al 11 in this supplement).…”
Section: Introductionmentioning
confidence: 99%